1997
DOI: 10.1002/clc.4960200912
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between exercise hyperpnea, hemodynamics, and blood gases before and during glyceryl trinitrate infusion in patients with exercise‐induced elevation of pulmonary artery wedge pressure

Abstract: SummaryBackground: The mechanisms underlying the excessive ventilatory response to exercise in patients with cardiac failure are still not fully understood.Hypothesis: This study was undertaken to investigate the mechanisms behind exercise hyperpnea in patients with exercise-induced left ventricular dysfunction.Methods: In 18 patients, aged 57-82 years, all with atherosclerotic lumbar aorta aneurysm and pulmonary artery wedge pressure (PAWP) >25 mmHg during supine exercise, ventila-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…1), but no reduction of the hyperpnoea. This is in line with the effects of acute medical treatment in similar patients during supine exercise ( Jørgensen et al ., 1997 , 1999), indicting that the excessive ventilatory response is unrelated to acute pulmonary congestion.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…1), but no reduction of the hyperpnoea. This is in line with the effects of acute medical treatment in similar patients during supine exercise ( Jørgensen et al ., 1997 , 1999), indicting that the excessive ventilatory response is unrelated to acute pulmonary congestion.…”
Section: Discussionsupporting
confidence: 88%
“…The relationships between high V˙ / V˙ O 2 and low P v O 2 during lying and sitting exercise in the LHD patients ( Fig. 2) fit in with recent suggestions that the excessive ventilation is caused by a combination of signals from hypoxia‐induced disturbances in peripheral tissues, particularly in the working muscles ( Barlow et al ., 1994 ; Clark & Coats, 1994; Clark et al ., 1995 ; Sullivan & Hawthorne, 1995; Harrington & Coats, 1997; Jørgensen et al ., 1997 ; 1999), and augmented muscle ergo‐reflex and peripheral and central chemoreceptor activity ( Chua et al ., 1996 ; Piepoli et al ., 1996 ; 1999). However, the low exercise P v O 2 in the LHD patients reflects a poor CO response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated a close association between exertional hyperpnoea and cardiac dysfunction ( Clark & Coats, 1994; Sullivan & Hawthorne, 1995; Jørgensen et al ., 1997 ; Jørgensen et al ., 1999 ). Accordingly, the fact that part of the excessive ventilatory response to exercise observed pre‐operatively persisted after elimination of the peripheral vascular insufficiency, was probably because the patients showed distinct evidence of left heart disease, with marked left ventricular dysfunction during moderate exercise.…”
Section: Discussionmentioning
confidence: 99%